Efficacy Dependence of Photodynamic Therapy Mediated by Upconversion Nanoparticles: Subcellular Positioning and Irradiation Productivity. Issue 13 (6th January 2017) - Chen, Dexin; Tao, Ran; Tao, Ke; Chen, Biqiong; Choi, Seok Ki; Tian, Qing; Xu, Yawen; Zhou, Guangdong; Sun, Kang
Abstract : Singlet oxygen ( 1 O2 ), as an important kind of reactive oxygen species (ROS) and main therapeutic agent in photodynamic therapy (PDT), only have a half‐life of 40 ns and an effective radius of 20 nm, which cause significant obstacles for improving PDT efficacy. In this work, novel upconversion nanoparticle (UCN)‐based nanoplatforms are developed with a minimized distance between UCNs and a photosensitizer, protoporphyrin IX (PpIX), and a controllable payload of PpIX, to enhance and control ROS production. The ability of the nanoplatform to target different subcellular organelles such as cell membrane and mitochondria is demonstrated via surface modification of the nanoplatform with different targeting ligands. The results show that the mitochondria‐targeting nanoplatforms result in significantly increased capability of both tumor cell killing and inhibition of tumor growth. Subcellular targeting of nanoparticles leads to the death of cancer cells in different manners. However, the efficiency of ROS generation almost have no influence on the tumor cell viability during the period of evaluation. These findings suggest that specific subcellular targeting of the nanoplatforms enhances the PDT efficacy more effectively than the increase of ROS production, and may shed light on future novel designs of effective and controllable PDT nanoplatforms. Abstract : Novel nanoplatforms for photodynamic therapy (PDT) are developed, featuring with a thin coating layer minimizing energy transfer distance, controllable photosensitizer payload, and capability of surface modification for organelle targeting. Targeting the reactive oxygen species (ROS) producing nanoplatform to mitochondria is found more effective than optimizing ROS production for improving PDT efficacy. The findings may provide a novel strategy for designing nanomedicine for PDT.